Microsoft Expression Web 2 on demand - Johnson, Steve, 1961- (Que Pub., 2008)
Microsoft Expression Web 2 on Demand FOR THOSE WHO WOULD RATHER BE SHOWN HOW THAN TOLD HOW SEE HOW TO • Create Web sites using drag and drop controls • Insert Flash, Windows Media, and Photoshop content • Create Cascading Style Sheet layouts • Integrate media and interactive Web applications using Microsoft Silverlight • Create a page design using layout tables • Explore the capabilities of Microsoft Expression Studio • Add interactive buttons and create hyperlinks • Create dynamic Web templates to reuse • Create forms to gather online information • Write, edit, and optimize code and scripts • Use IntelliSense to help reduce coding errors • Retrieve and present data from live RSS feeds • Integrate data from databases or XML data • Create dynamic Web content using ASP.NET technology On the Web This book uses real world examples to give you a context in which to use the task. This book also includes workshops to help you put together individual tasks into projects. The Expression Web 2 example files that you need for project tasks are available at www.perspection.com Perspection has written and produced books on a variety of computer software, including Adobe Flash CS3 and 8, Adobe Photoshop CS3 and CS2, Adobe Dreamweaver CS3, Microsoft Office 2007 and 2003, Microsoft Windows Vista and XP, Microsoft Expression Web, and Apple Mac OS X Leopard. Perspection was founded in 1991, and is committed to providing information and training to help people use software more effectively. Perspection has written more than 80 computer books, and sold more than 5 million copies.